2018
DOI: 10.1136/bcr-2017-223887
|View full text |Cite
|
Sign up to set email alerts
|

Pancytopenia: a rare complication of Graves’ disease

Abstract: A 27-year-old male patient who presented to the emergency room with complaints of sweating, palpitations, heat intolerance, insomnia and weight loss for the last 3 months. His medical history was significant for hypertension. On examination, he was tachycardic, hypertensive, had tremors of the upper extremities and a smooth goitre with a thyroid bruit. Laboratory assessment revealed a suppressed thyroid-stimulating hormone, high free thyroxine and positive thyroid receptor antibodies. Complete blood count show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 21 publications
0
29
0
1
Order By: Relevance
“…There have been 14 reported cases in the literature of pancytopenia associated with thyrotoxicosis in GD. Although the mechanisms remain to be fully delineated, it is hypothesized that pancytopenia results from either decreased production of hematopoietic cells or increased destruction (1). In our patient, pancytopenia nearly entirely resolved following treatment of the vitamin B 12 deficiency, while thyrotoxicosis persisted.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…There have been 14 reported cases in the literature of pancytopenia associated with thyrotoxicosis in GD. Although the mechanisms remain to be fully delineated, it is hypothesized that pancytopenia results from either decreased production of hematopoietic cells or increased destruction (1). In our patient, pancytopenia nearly entirely resolved following treatment of the vitamin B 12 deficiency, while thyrotoxicosis persisted.…”
Section: Discussionmentioning
confidence: 69%
“…Graves disease (GD) is an autoimmune process in which thyrotropin receptor antibodies stimulate thyrotropin receptors on the thyroid, leading to hyperthyroidism (1). Hyperthyroidism can affect all blood cell lineages through a variety of mechanisms leading to anemia, thrombocytopenia, leukopenia, and in rare instances pancytopenia (1)(2)(3)(4)(5). Likewise, use of antithyroid drugs (ATDs) for management of thyrotoxicosis is associated with a variety of hematopoietic abnormalities including agranulocytosis and pancytopenia (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GD with pancytopenia has been described rarely in literature. [456789] Single-lineage abnormalities are more common in patients with hyperthyroidism. In hyperthyroidism, anemia, leukopenia, or thrombocytopenia occurs in approximately 34%, 5.8%, and 3.3% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary anemia associated with hyperthyroidism is a relatively rare complication [1]. Many reports have shown that although anemia progresses with hyperthyroidism in Graves' disease, it is often transient, improving with treatment of Graves' disease [2,3].…”
Section: Introductionmentioning
confidence: 99%